On applications of the extended Jack’s lemma
UDC 517.5 We introduce and study a class G (α,β) comprising analytic functions associated with a sector domain, where α,β(0,1]. By using the extended version of Jack’s lemma, we deduce the Open–Door lemma sufficient conditions for functions to be in G (α,β). Furthermore, we present special cases of our results that are in agreement with known results. , number=6, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Kumar, S. Sivaprasad and Yadav, Pooja, year=2025, month=Aug., pages=449–450